ANALISIS PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Maryanti, Eny (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study was to analyze the profitability, growth, sales growth and asset structure of the company on capital structure. The research object was the entire industrial sector of consumer goods amounted to 36 companies, but based on the completeness of the data, then, only 30 companies takan as samples with the observation period of 2012-2014. The independent variables were profitability, growth, sales growth and asset structure while the dependent variable was capital structure (debt to total assets ratio). The data analysis used multiple linear regressions. These results indicate that the growth of the company have a significant effect on the capital structure. Profitability, sales growth and asset structure has no effect on the capital structure. Key Words : Profitability, Growth of Company, Asset Structure Of The Company, Sales Growth, Capital Structure